Iron Reduces Iron: A Spectroelectrochemical Insight of Ligand Effect on Iron Redox Potential - Shabnum Bashir (Science Faculty of Chiang Mai University, 2019)
The electron transfer reaction between two oxidation states of a transition metal redox couple is amazingly interesting. The present study describes a combined spectropho- tometric and potentiometric investigation of redox reaction involving iron (III) and iron(II) oxidation states. The electron transfer reaction is seen to occur between iron-(III)phenanthroline complex and a series of iron-(II) complexes with water, EDTA, DPTA, NTA, Tiron and diphosphate ligands. The relative propensity of selected ligands towards this reaction, displayed in the potentiometric titration plots can be corroborated with the redox potential modification of Fe(III)-Fe(II) redox couple. The ligand effect on redox potential of the iron redox couple as the underlying concept of the reaction, has been thoroughly investigated and thermodynamically modeled. The differing abilities of EDTA and Tiron ligands towards the spontaneity of this reaction under different pH conditions were potentiometerically observed and spectrophotometrically rationalized with the degree of ligand chelation vis-a-vis complex stability and the resultant redox potential. The experiment can serve as a model for unique environmental and biological redox reactions and can be explored further for designing of novel redox systems for redox flow cells.